PEMBERDAYAAN MASYARAKAT DESA NEGERI LAMA SEBERANG MELALUI PELATIHAN PEMBUATAN RENGGINANG SEBAGAI HOME INDUSTRY - Fitria, Indah; Ariani Hrp, Nurlina; Fitria Andika, Novi; Hasibuan, Lili Rohanita (LP2M IAIN Sultan Amai Gorontalo, 2021)
This activity aims to empower the community in improving the economy through home industry in the village of Negeri Lama Seberang. Based on the background of the village which is a village with a large population as farmers. The lack of activities of housewives in the village became the target of activities to provide knowledge about economic improvement through home industry. Activities in this empowerment program are based on two existing potentials, namely in terms of natural resources and human resources in the village of Negeri Lama Seberang. The form of activity is to provide training to make Rengginang as a home industry business in order to utilize natural resources from abundant agricultural products, namely pulut rice. In addition to being sold in the village area of ​​Negeri Lama Seberang, the product from the pulut rice harvest has motivated the community to optimize the harvest into other products which in this case are rengginang products. This activity is considered to be able to increase the level of welfare and economic prosperity of the community through the establishment of a home industry. The success of the community empowerment program to increase the income of the village community in Negeri Lama Seberang is influenced by the conditions and local wisdom that are available adequately.